2017
DOI: 10.1097/ajp.0000000000000412
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Transversus Abdominis Plane (TAP) Block in Hernia Surgery

Abstract: Within a heterogeneous group of RCTs, TAP block reduces postoperative morphine requirements and the severity of pain after hernia surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 36 publications
0
27
1
4
Order By: Relevance
“…In general, it has been frequently elaborated that the TAP block may lead to a reduced analgesic use following IHR [ 3 , 20 ]. To our knowledge, the IVG and UG have not been compared further to one another in terms of analgesic use postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…In general, it has been frequently elaborated that the TAP block may lead to a reduced analgesic use following IHR [ 3 , 20 ]. To our knowledge, the IVG and UG have not been compared further to one another in terms of analgesic use postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple systematic reviews have confirmed the analgesic efficacy of TAP block for open and laparoscopic colorectal surgeries [38, 39, 40•, 41-43]. Similarly, ultrasound-guided TAP block has been found to be an effective analgesic intervention in patients undergoing laparoscopic cholecystectomy [44,45] and hernia surgery [46]. TAP blocks have also been shown to significantly lower intraoperative and cumulative postoperative 24-h opioid consumption, provide better pain control, and decrease the 24-h incidence of postoperative nausea vomiting for renal transplant recipients [47].…”
Section: Tap Blocks Versus No Block/placebomentioning
confidence: 99%
“…Thus, there was a surge of interest in TAP blocks as therapeutic adjuncts for analgesia after abdominal surgeries. In the past decade, there has been growing evidence supporting the effectiveness of TAP blocks for a variety of abdominal surgeries, such as cesarean section, hysterectomy, cholecystectomy, colectomy, prostatectomy, and hernia repair [ 1 , 3 9 ]. Although its analgesic effect covers only somatic pain with short duration [ 10 ], single-shot TAP block plays a valuable role in multimodal analgesia.…”
Section: Introductionmentioning
confidence: 99%